THE INFLUENCE OF FINANCIAL LITERACY AND LIFESTYLE ON FINANCIAL MANAGEMENT BEHAVIOR IN STUDENTS (CASE STUDY OF STUDENTS IN LAHAT DISTRICT) - Oktala, Rosananda; Yulanda, Delvina; Raparaeni, Yusi; Lestari, Dwi (Jurnal Manajemen, 2024)
Financial literacy and lifestyle have an important role in determining wise financial management behavior in students. Through good knowledge can encourage students to make the right and efficient decisions in the use or allocation of funds owned so as to achieve individual financial welfare. This study aims to determine how financial literacy and lifestyle influence the financial management behavior of students in Lahat district. Data collection was carried out by distributing questionnaires to 66 students in Lahat Regency. Based on the analysis, it shows that financial literacy is not proven to affect student financial management behavior, but lifestyle is proven to significantly affect student financial management behavior. Students with a consumptive lifestyle will find it more difficult to manage finances that can lead to financial problems in the future.